Microclimatic Variations in Dachhigam Sanctuary, Kashmir - Singh, Gurcharan; Kachroo, P. (Indian Forester, 1976)
Three microclimatic factors; soil temperature, air temperatare and soil moisture are considered for their interrelationships and variations as influenced by altitude, topography and plant cover, within an altitudinal range of 1,700-2,300 m, in Dachhigam sanctuary Kashmir. An increase in soil moisture and decrease in temperatures is exhibited with altitudinal increase, shift from southern to northern exposure and from herbaceous to tree cover. Seasonal influences of these factors are also considered based upon weekly data.